Diagnosis of Lung Cancer by FTIR Spectroscopy Combined With Raman Spectroscopy Based on Data Fusion and Wavelet Transform - Yang, Xien; Wu, Zhongyu; Ou, Quanhong; Qian, Kai; Jiang, Liqin; Yang, Weiye; Shi, Youming; Liu, Gang (Frontiers in Chemistry, 2022)
Lung cancer is a fatal tumor threatening human health. It is of great significance to explore a diagnostic method with wide application range, high specificity and high sensitivity for the detection of lung cancer. In this paper, data fusion and wavelet transform were used in combination with Fourier transform infrared (FTIR) spectroscopy and Raman spectroscopy to study the serum samples of patients with lung cancer and healthy people. The Raman spectra of serum samples can provide more biological information than the FTIR spectra of serum samples. After selecting the optimal wavelet parameters for wavelet threshold denoising (WTD) of spectral data, partial least squares-discriminant analysis (PLS-DA) model showed 93.41% accuracy, 96.08% specificity and 90% sensitivity for the fusion data processed by WTD in the prediction set. The results showed that the combination of FTIR spectroscopy and Raman spectroscopy based on data fusion and wavelet transform can effectively diagnose the patients with lung cancer, and is expected to be applied to clinical screening and diagnosis in the future.